Economic design of a CEV x̄ control chart for determining optimal right-censored times. Issue 4 (4th July 2021) - Lee, Pei-Hsi
ABSTRACT: Lifetime is a crucial quality characteristic of electronic products that must be monitored using control charts. Lifetime may provide right-censored data. A conditional expected value (CEV) x̄ control chart was developed to monitor type I right-censored data. Researchers had always assumed that the censored time is a known constant when designing control charts. This study provides an economic design model for optimizing CEV x̄ charts and type I right-censored time for reducing costs associated with quality control and life tests. This method was employed on a practical case of a liquid crystal display module. A sensitivity analysis was also conducted on the influence of the model parameters on the design and censored time of the CEV x̄ chart.